Subfossil Cladocera as a powerful tool for paleoecological reconstruction - Monica Tolotti; Manuela Milan; Krystyna Szeroczyńska (Advances in Oceanography and Limnology, 2016)
Subfossil Cladocera (Crustacea, Branchiopoda) represent one of the most valuable biological proxies preserved in lake sediments that can be studied for reconstruction purposes. They are widespread in both the pelagic and littoral zones of lakes of different geographical distribution, altitude and typology, where they often represent the dominant component of zooplankton in terms of biomass. The chitinous parts of their body are well preserved in lake sediments, and the taphonomic taxonomy is well established, thanks to the numerous studies that followed the first pioneer works by Frey (1960).